Recent Advances in Molecular Pharmacology of the Histamine Systems: Immune Regulatory Roles of Histamine Produced by Leukocytes - Tanaka Satoshi; Ichikawa Atsushi (Elsevier, 2006)
Abstract.: Accumulating evidence has highlighted the importance of histamine in immune responses. The H1 receptor is involved not only in allergic inflammatory reactions but also in augmentation of helper T cell (Th)1 responses, whereas H2 receptor suppresses Th responses and participates in immune tolerance through interleukin-10 and transforming growth factor-β. Identification of the H4 receptor, which binds to histamine with high affinity and of which expression is limited to the hematopoietic system, has enhanced the importance of histamine in immune responses. However, since a majority of previous studies has evaluated the effects of exogenous histamine, it remains largely unknown how endogenously produced histamine is involved in regulation of such kinds of immune responses. Insight into precise roles of histamine in the immune system can not be obtained without correct understanding of both the predominance of a certain type of histamine receptor and the regulation of histamine synthesis. Here we review a part of the recent progress in histamine research in the field of immunology with attention to the source of involved histamine. Keywords:: mast cell, IgE, histamine, histidine decarboxylase